Reform and punishment: an overview of correctional rehabilitation in mainland China - Wang, Yixuan (Approaches to offender rehabilitation in Asian jurisdictions, 2024)
Over the past few decades, rehabilitation has competed with the traditional punitive paradigm in correctional theory and institutional practice. However, theoretical orientation and practice vary across jurisdictions and cultural settings. These variations have not been well studied and understood, particularly in non-Western countries such as China, which has a different cultural tradition and history of development leading to the current orientation and practices. This chapter shows that despite official declarations that punishment is not the goal and means of correctional services, rehabilitation and punishment are intertwined. This chapter describes the evolution and current framework for rehabilitation practices in China, and its plans for improvement.